The Combined Role of Self-Esteem and Life Satisfaction in Enhancing Student Engagement - Savitri, Jane; Kiswantomo, Heliany; Tambun, Grace Naulee (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
Student engagement is essential for academic success and holistic development, yet many studies have examined only isolated predictors of engagement. While self-esteem and life satisfaction have each been linked to engagement, few studies have investigated their combined effect, particularly within non-Western contexts such as Indonesia. Addressing this gap, the present study examines the joint and individual contributions of self-esteem and life satisfaction to student engagement among 397 active university students in Bandung City. Using a quantitative correlational design, data were collected through the University Student Engagement Inventory (USEI), the Rosenberg Self-Esteem Scale (RSES), and the Satisfaction with Life Scale (SWLS). Multiple regression analysis revealed that self-esteem and life satisfaction significantly predicted student engagement, both independently and simultaneously (R² = 0.31, p < .001). Self-esteem emerged as the stronger predictor, accounting for 21.3% of the variance, compared to 9.7% from life satisfaction. These findings underscore the importance of fostering both self-esteem and life satisfaction in educational settings to enhance student engagement. The study contributes a novel perspective by demonstrating the synergistic influence of these two psychological factors in a culturally specific context. Practical implications include the need for integrated student development programs that promote self-worth and subjective well-being. The study calls for future research to examine how each predictor influences different dimensions of engagement—behavioral, emotional, and cognitive—over time.